INTEGRATED MARKETING COMMUNICATION STRATEGY IN INCREASING SALES IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Loso Judijanto; Kristopo; Edy Setyo Wibowo (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to examine Integrated Marketing Communication (IMC) strategies in the context of Micro, Small and Medium Enterprises (MSMEs) and their impact on increasing sales. Through a comprehensive literature review, this study analyzes various aspects of IMC implementation in MSMEs, including challenges, opportunities and best practices that can be adopted. The method used in this research is systematic literature analysis, utilizing the latest scientific sources such as academic journals, industry reports and relevant case studies. The main focus of the research is on the period 2010-2023, covering the latest developments in digital marketing strategies and their impact on MSMEs. The research results show that effective IMC implementation can significantly increase MSME sales through several key mechanisms: (1) increasing brand awareness, (2) marketing cost efficiency, (3) increasing customer engagement, and (4) optimizing marketing channels. However, research also identifies several key challenges that MSMEs face in adopting IMC, including limited resources, lack of technical expertise, and difficulties in measuring return on investment (ROI). The study concludes that despite the challenges, IMC offers significant potential for MSMEs to increase their competitiveness and sales. The proposed recommendations include a gradual approach in implementing IMC, a focus on cost-effective use of digital technology, and developing the internal capacity of MSMEs in planning and executing integrated marketing strategies.